THE EFFECTIVENESS OF LIME (Citrus aurantifolia) SOLUTION ON QUALITY OF Pterygoplichthys pardalis FLESH FROM CILIWUNG RIVER, JAKARTA, INDONESIA - Nanda Vindi Aini; Dewi Elfidasari; Irawan Sugoro (International Journal of Biosciences and Biotechnology, 2022)
Rivers play an important role in life, but they are highly polluted by increased activities in the surrounding. For example, Ciliwung River is experiencing heavy metal pollution which has affected aquatic organisms including the pleco fish widely used by local communities as food ingredients such as dumplings, dimsum, and otak-otak. This element’s content rises in pleco fish flesh yearly and the accumulation after entering the human body interferes with health. Even though the usage of citric acid-containing lime reduces heavy metals, currently, no information explains the fruit’s effectiveness on metal content in pleco fish. Therefore, this research aims to prove the effectiveness of lime solution on pleco fish flesh quality. It was conducted by soaking the fish flesh with control and the lime solution at different concentrations, namely 0, 50, 75, and 100% for 10 and 30 minutes. Proximate analysis was performed followed by metal and mineral content testing through the XRF method. Based on the results, soaking the sample object with a higher concentration of lime and at a longer time caused a decrease in ash content, while water, protein, and fat increased. After soaking, Pb and Hg content had chelation in each treatment but still exceeded the SNI threshold value, while Sn was in accordance with the SNI. The content of macrominerals (K, Cl, Mg, and P) and microminerals (Cu, Zn, and Se) became different.